"Because you always learn something new yourself!" An expectancy-value-theory perspective on mentor teachers' initial motivations. (May 2022) - Kuhn, Clara; Hagenauer, Gerda; Gröschner, Alexander
Abstract: A teacher's decision to become a mentor teacher affects mentoring quality and the practicum experience of student teachers respectively. However, little systematic knowledge about teachers' motivations to become mentors exists to date. Based on expectancy-value theory (EVT), this interview study among 23 secondary school mentor teachers explores which aspects motivate teachers to undertake the task of mentoring. In line with EVT, teachers choose to become mentors due to a combination of expectancy and value beliefs, and socialisation influences, which can be further categorised into competence beliefs, intrinsic values, social utility values, intrinsic and extrinsic personal utility values, and social influences. Highlights: Expectancy-value theory is a fruitful theoretical framework to investigate teachers' motivations to become mentor teachers. Participants believe they benefit from mentoring through mutually learning from each other. Personal utility values within the mentoring context can be categorised into intrinsic and extrinsic dimensions. Participants indicate that social utility values are a core motivator for becoming a mentor teacher.